Transformational Leadership and Job Performance: The Mediating Role of Work Engagement - Lai, Fong-Yi; Tang, Hui-Chuan; Lu, Szu-Chi; Lee, Yu-Chin; Lin, Cheng-Chen (SAGE open, 2020)
This study proposed that transformational leaders use various behaviors to provoke followers’ organizationally beneficial behaviors (e.g., better task performance and helping behaviors) through ignition of followers’ work engagement. That is, employees who inspired by transformational leadership are more likely to immerse themselves in the work, and, in turn, this is likely to result in better task performance and helping behaviors. In this study, we adopted a multitemporal and multisource research design to reduce the consideration of common method variance. Hypotheses were tested on a sample of 507 nurses working in 44 teams. The hierarchical linear regression analysis showed that, after controlling for several relevant variables (e.g., leader–member exchange [LMX], role-based self-efficacy, and transactional leadership) and several participants’ demographic variables (e.g., gender, age, and education), work engagement still mediates the positive relationship among transformational leadership, job performance, and helping behavior. Strengths, limitations, practical implications, and directions for future research are discussed.